Reactions of epoxidized natural rubber with palm oil-based alkyds and medium-chain-lenght polyhydroxyalkanoates / Lee Siang Yin - Lee, Siang Yin (2009)
Actinomycetes are widespread in marine ecosystem. They are of interest in research field as they are capable to produce bioactive secondary metabolites which can be developed into useful pharmaceutical products. An example of the product is antibiotics which can be used to treat infectious diseases. The potential of antibacterial and antifungal activity of eleven marine derived actinomycetes from the genus Streptomyces were studied. They were tested against bacteria Enterobacter faecalis, Staphylococcus aureus, Bacillus subtilis, Pleisiomonas shigelloides and Pseudomonas aeruginosa and fungi Candida parapsilosis and Candida albicans. Primary screening by the cross streak method and secondary screening by diffusion using paper disc method with crude extracts were carried out in this study. Media optimization was also carried out to optimize the media for production of bioactive secondary metabolites. Of the eleven strains studied, strain T53 exhibited the strongest antibacterial activity against E. faecalis. Gram-positive bacteria were more susceptible than Gram-negative bacteria. Strain T53, T52, T9 and T12 had broad spectrum activities. Strain T53, T16,T15 and T4 exhibited antifungal activity against all tested fungi. Yeast extract-malt extract agar (ISP2) and agitated fermentation were the best media and the best fermentation condition, respectively.